Strain‐Mediated Phase Stabilization: A New Strategy for Ultrastable α‐CsPbI3 Perovskite by Nanoconfined Growth. Issue 21 (4th April 2019) - Ma, Sunihl; Kim, Seong Hun; Jeong, Beomjin; Kwon, Hyeok‐Chan; Yun, Seong‐Cheol; Jang, Gyumin; Yang, Hyunha; Park, Cheolmin; Lee, Donghwa; Moon, Jooho
Abstract: All‐inorganic cesium lead triiodide (CsPbI3 ) perovskite is considered a promising solution‐processable semiconductor for highly stable optoelectronic and photovoltaic applications. However, despite its excellent optoelectronic properties, the phase instability of CsPbI3 poses a critical hurdle for practical application. In this study, a novel stain‐mediated phase stabilization strategy is demonstrated to significantly enhance the phase stability of cubic α‐phase CsPbI3 . Careful control of the degree of spatial confinement induced by anodized aluminum oxide (AAO) templates with varying pore sizes leads to effective manipulation of the phase stability of α‐CsPbI3 . The Williamson–Hall method in conjunction with density functional theory calculations clearly confirms that the strain imposed on the perovskite lattice when confined in vertically aligned nanopores can alter the formation energy of the system, stabilizing α‐CsPbI3 at room temperature. Finally, the CsPbI3 grown inside nanoporous AAO templates exhibits exceptional phase stability over three months under ambient conditions, in which the resulting light‐emitting diode reveals a natural red color emission with very narrow bandwidth (full width at half maximum of 33 nm) at 702 nm. The universally applicable template‐based stabilization strategy can give in‐depth insights on the strain‐mediated phase transition mechanism in all‐inorganic perovskites. Abstract : A novel approach to stabilize α‐CsPbI3 perovskite through strain engineering, whereby CsPbI3 perovskite is confined by a vertically aligned nanoporous template, is developed. By imposing a strain on the perovskite lattice, the ultrastable black α‐CsPbI3 with its desirable optoelectrical properties is obtained. The density functional theory calculations on the formation energy confirm that the strain‐mediated phase stabilization is thermodynamically allowed.